Cumhuriyetin 100. Yılında Geçmişten Geleceğe Nazilli-2023 - Güneş, Günver; Adalığ, Bingül; Çınar, Semih; Akdağ, Menderes; Bigat Akça, Büşra; Yenipazarlı, Aslı; Başkaya, Hatice; Özdemir, Abdullah; Tuncer, İ. Kaya and Yılmaz, Şahin Efe and Öden, İlhan and Genç, Fatma Neval and Aksoy, Esra and Berber Babalık, Banu and Çan Domruk, Yeter and Kürüm, Mükerrem and Haykıran, Kemal Ramazan and Özdemir, Yasin and Gökçe, Evren and Pullukçuoğlu Yapucu, Olcay and Hamaloğlu, İbrahim and Özgün, Cihan and Şahin, Mustafa Kemal and Sina, Ayşen and Üreten, Hüseyin and Özaltın, Oğuzhan and Akova Havalı, Sibel and Çiftçi, Kenan (Academician Publishing Book DOI Portal, 2024)
-